The construction of mainline works at Sungai Besi - Ulu Kelang Highway (SUKE) privatization project / Nurul Izzah Balqish Yusnee - Yusnee, Nurul Izzah Balqish (Universiti Teknologi MARA UiTM,Perak, 2022)
Stephen Gardiner once said, "Good buildings come from good people, and all problems are solved by good design." This report discusses the pipe jacking and grouting methods used to create an effective drainage system in a particular area. Pipe jacking is a method of constructing underground pipes and drainage systems. It is often called as microtunnelling but in a smaller size. Practical engineering concerns and economics may limit the use of individual pipe jacks. Continue to the following technique, grouting. Injection grouting is a technique that entails injecting a material under pressure into cracks, open joints, voids, or honeycombs in concrete or masonry structural components to fulfill certain goals. The report's main objective is to know the exact term and purpose of all contract components in order to accomplish a project effectively. Additionally, to discover the specific methodology for pipe jacking and grouting operation, as well as their method description along with to have a better understanding of the benefits and drawbacks of the pipe jacking and grouting work methods. In conclusion, in today 's environment, choosing the accurate material and technique for pipe jacking operation is crucial to have an efficient drainage system that can be used for a long period of time especially when flooding season arise in Malaysia